Nanostructured lipid carrier surface modified with Eudragit RS 100 and its potential ophthalmic functions - Zhang W (Dove Medical Press, 2014)
Wenji Zhang,1,3,* Xuedong Li,2,* Tiantian Ye,3 Fen Chen,3 Shihui Yu,3 Jianting Chen,3 Xinggang Yang,3 Na Yang,2 Jinsong Zhang,2 Jinlu Liu,2 Weisan Pan,3 Jun Kong2 1Department of Pharmaceutics, School of Traditional Chinese Medicine, Shenyang Pharmaceutical University, Shenyang, People’s Republic of China; 2Department of Ophthalmology, The Fourth Affiliated Hospital of China Medical University, Eye Hospital of China Medical University, Key Lens Research Laboratory of Liaoning Province, Shenyang, People’s Republic of China; 3Department of Pharmaceutics, School of Pharmacy, Shenyang Pharmaceutical University, Shenyang, People’s Republic of China *These authors contributed equally to this work Abstract: This study was carried out to evaluate the ocular performance of a cationic Eudragit (EDU) RS 100-coated nanostructured lipid carrier (NLC). The genistein encapsulated NLC (GEN-NLC) was produced using the melt-emulsification technique followed by surface absorption of EDU RS 100. The EDU RS 100 increased the surface zeta potential from −7.46 mV to +13.60 mV, by uniformly forming a spherical coating outside the NLC surface, as shown by transmission electron microscopy images. The EDU RS 100 on the NLC surface effectively improved the NLC stability by inhibiting particle size growth. The obtained EDU RS 100-GEN-NLC showed extended precorneal clearance and a 1.22-fold increase in AUC (area under the curve) compared with the bare NLC in a Gamma scintigraphic evaluation. The EDU RS 100 modification also significantly increased corneal penetration producing a 3.3-fold increase in apparent permeability coefficients (Papp) compared with references. Draize and cytotoxicity testing confirmed that the developed EDU RS 100-GEN-NLC was nonirritant to ocular tissues and nontoxic to corneal cells. These results indicate that the NLC surface modified by EDU RS 100 significantly improves the NLC properties and exhibits many advantages for ocular use. Keywords: genistein, precorneal retention, cytotoxicity